Obstacles to the exercise of sports activity at the University of Basra From the students' point of view Survey research - Dr. Nahida Abdel - Zahra Badr,; Assist Lecturer. Roua Mohammed Al - Madh,; Assist Lecturer.Waleed Latif Maird, (University of Thi-Qar Journal, 2019)
The university is one of the most important educational institutions in the developed countries. In order for us in a country that seeks to develop, we can promote these educational institutions. We must give them their right in all fields, especially physical education. The researchers want to focus on an important aspect, namely, the student's practice of sports activity within the University of Basrah, where its importance is no less than other scientific lessons in the other countries of the developed world is the most important mathematical activity in the evaluation of the student morally, physically and psychologically and that the cancellation of these activities and marginalization is very dangerous because The exercise of sports activity is important at all ages, especially that our society today urgently need to create healthy habits, physical and intellectual civilized to build the individual building intact away from the tragedies of wars and the legacy of the wrong practices and the importance of this activity must consider the reasons that stand in the way In front of the students at the University of Basra, especially at this time, where we seek to attract them to practice sports activities, especially at this time period experienced by our country. The aim of this research is to prepare for the correct formation of the society.